BODILY COMPOSITION AND BODY TYPES OF TEENAGE TENNIS PLAYERS IN GREECEA STUDY - Vasileios KORONAS (Editura Universitatii Transilvania din Brasov, 2019)
This article focuses on an assessment of the overall health and bodily condition of teenage tennis players in Greece. The researcher attempted to assess the different body types and characteristics and the impact they have on the performance of young tennis players. In this study, the focus is places on young tennis players, through a comparison of real data, in an effort to discover similarities and differences in the bodily composition and body types of athletes aged 12-16 years in Greece who have chosen tennis as their sport of preference and trained by coaches. The results have been analyzed with the use of SPSS.